Acute kidney injury predicts mortality in cirrhotic patients with gastric variceal bleeding. Issue 11 (10th October 2017) - Hsieh, Yun‐Cheng; Lee, Kuei‐Chuan; Chen, Ping‐Hsien; Su, Chien‐Wei; Hou, Ming‐Chih; Lin, Han‐Chieh
Abstract: Background and Aim: The International Club of Ascites (ICA) recently proposed a new definition of acute kidney injury (AKI) in cirrhotic patients. The study evaluated the ICA‐AKI criteria and their association with the prognosis of cirrhotic patients with gastric variceal bleeding (GVB). Methods: A retrospective cohort study using prospective database of cirrhotic patients hospitalized with the first presentation of acute GVB at Taipei Veterans General Hospital from April 2007 to December 2010 was performed to evaluate the development of AKI. The study used Cox proportional hazards model to examine the association of ICA‐AKI criteria and mortality. Results: Of 113 patients, 46 (41%) fulfilled the ICA‐AKI criteria and most (70%) initially had stage 1 AKI. Child‐Pugh score, systemic blood pressure at admission, and number of blood units transfused before endoscopy were independent predictors of AKI. Among patients with AKI, 30% progressed to higher stages with more advanced liver disease, lower serum sodium, more units of blood transfusion, higher frequency of infection, and higher serum creatinine levels at diagnosis of AKI. The 6‐week mortality rate was significantly higher in patients with AKI than in patients without AKI (37% vs 3%, P  < 0.001), and AKI stages were independent predictors of 3‐month survival (93% in patients without AKI, 73% in stage 1, and 30% in stages 2 and 3, P  = 0.005). Conclusions: The occurrence of AKI as defined by the ICA criteria is common in cirrhotic patients with acute GVB. The presence of AKI was associated with much higher 6‐week mortality, and the stages of AKI further predicted 3‐month survival.